Application of the OPG in the prediction of unfavorably angulated canines: An original study - Faisal M Ansari; K T Naseem; Amrita Ashok; T K Bavitha; V Fawaz; Jibin K Sabu (Wolters Kluwer Medknow Publications, 2023)
Introduction: Achieving a correct occlusion depends heavily on the axial inclination of the teeth, particularly the maxillary anteriors, which have the longest crowns. This study, which expanded the use of angular measures to the mandible, was created to determine the prevalence of adversely angulated canines using orthopantomograms. Methods: A sample of 200 people between the ages of 18 and 25 was chosen and separated into two groups based on the degree of crowding; one group served as the control group while the other, which experienced severe, crowding, served as the study group. All of the individuals had their Orthopantomogram and study models taken. Results: While canine angulation in controls typically ranges from 85 to 95 degrees, cases of crowding were observed to have angulation as low as 67 degrees and as high as 105 degrees. Conclusion: Orthopantomogram can be used to predict canine angulation, with distally and mesially angulated canines occurring at rates of roughly 18% and 37%, respectively.